Individual and Classroom Social-Cognitive Processes in Bullying: A Short-Term Longitudinal Multilevel Study - Thornberg, Robert; Wänström, Linda; Hymel, Shelley (Frontiers in Psychology, 2019)
The aim of this study was to examine whether individual and classroom collective social-cognitive processes (moral disengagement and self-efficacy) were associated with bullying perpetration among schoolchildren. An additional aim was to examine whether changes in these processes from grade 4 (Time 1) to grade 5 (Time 2) were associated with a change in bullying perpetration. Self-reported survey data were collected from 1,250 Swedish students from 98 classrooms. Results of multilevel analysis indicated that individual and classroom collective moral disengagement were positively associated with bullying, and defender self-efficacy was negatively associated with bullying. The effect of changes in individual moral disengagement on changes in bullying was positive, and the effects of changes in defender self-efficacy and classroom collective efficacy on changes in bullying were negative. Thus, the findings demonstrate the changeability of moral disengagement, defender self-efficacy and collective efficacy over time, and how these changes are linked to changes in bullying perpetration.